Redox Flow Capacitive Deionization in a Mixed Electrode Solvent of Water and Ethanol. Issue 1 (12th January 2022) - Tang, Lufan; Wei, Qiang; Yan, Jiawei; Hu, Yudi; Chen, Xuncai; Wang, Guannan; Aung, Su Htike; Oo, Than Zaw; Yan, Dongliang; Chen, Fuming
Abstract : In redox flow electrode capacitive deionization (FCDI), the solubility of the redox electrolyte and flowability of the carbon slurry have a great influence on the salt removal rate and energy consumption. In this work, a mixed solvent electrolyte is proposed for FCDI, which consists of iodide/triiodide redox couples and a carbon slurry in a mixed solvent of water and ethanol (1:1). At a current density of 5 mA cm −2, the salt removal rate in the mixed solvent can reach up to 2.72 μ g cm −2 s −1, which is much higher than the value of 1.74 μ g cm −2 s −1 and 2.37 μ g cm −2 s −1 obtained in aqueous and ethanol solutions, respectively. This is attributed to the fast transport of ions during the redox reaction in organic solvents and the excellent flowability of the carbon slurry under aqueous conditions, which can provide more reaction sites for iodide/triiodide redox reactions and faster electron transportation. This unique FCDI with organic and aqueous mixed solvent electrolytes provides a new perspective for the development of redox flow electrochemical desalination.